Analisa Penerapan Fitur Firewall pada Mikrotik untuk Mengamankan dari Serangan Denial of Service (DoS) - Wijaya, Frederico Indra; Innuddin, Muhammad; Latif, Kurniadin Abd. (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Cybercrimes such as Denial of Service (DoS) attacks pose a serious threat to the stability of computer networks, especially those without adequate protection. This study aims to analyze the implementation of firewall features on Mikrotik routers as an effort to improve network security against DoS attacks. The method used refers to the Network Development Life Cycle (NDLC) approach, which includes the stages of analysis, design, simulation, implementation, and testing. The results show that the firewall configuration successfully closed several vulnerable ports (FTP, SSH, Telnet, and HTTP) while maintaining critical operational ports (DNS and Winbox). Furthermore, the CPU load on the router decreased dramatically from 100% to 3-4% after implementation, indicating success in mitigating malicious traffic. These findings confirm that the firewall feature on Mikrotik can significantly increase network resilience against DoS attacks.